Context-Driven Multigranularity Blockchain: A Comprehensive Framework for Secure Data Management (International Journal of Innovative Research in Computer Science & Technology, 2023)
Effective access control and revocation  mechanisms are paramount in the ever-evolving  landscape of information security. Traditional models  often fall short in addressing the complexities of modern  systems, necessitating the integration of context-aware  decision-making and multi-granularity attributes. In this  manuscript, we propose a novel access control framework  leveraging the strengths of Attribute-Based Access  Control (ABAC) and Attribute-Based Encryption (ABE)  and blockchain technologies. The decentralized and  immutable nature of blockchain further bolsters the  trustworthiness of access control decisions. Our method  introduces context-awareness and multi-granularity  attributes into the decision-making process, enhancing  adaptability and responsiveness. Through extensive  experiments and comparisons with existing approaches,  our results demonstrate the superior performance of our  proposed method. This work not only contributes to the  theoretical foundations of access control but also provides  a practical solution that outperforms current state-of-the art methods, addressing the dynamic security challenges  of contemporary information systems.
Keywords: ABAC; ABE; Access Policies; Blockchain; Context Awareness; Revocation; Temporal and Spatial